Upaya-Upaya Supervisi Dalam Memonitoring Kinerja Guru Pendidikan Agama Kristen Di Sekolah - Wadison Petrus; Talizaro Tafonao; Agiana Her Visnhu Ditakristi (Vox Dei: Jurnal Teologi dan Pastoral, 2022)
The purpose of writing this article is to see the effectiveness of supervision in monitoring the performance of Christian Religious Education teachers in schools. The basic problem in this paper is that researchers still find some Christian Religious Education teachers who have not carried out their duties optimally based on the applicable rules. Based on the subject matter, the task of supervision seeks to carry out its functions as described in this article. The research method used in this study is a qualitative research method. The results obtained in this paper show that by observing, directing, coaching and checking administration, it has a very positive impact on the performance of teachers in schools and is more organized in carrying out their duties and carrying out their responsibilities in accordance with the main tasks they carry out. Thus, it seems that there are no teachers who are neglected and who neglect each of their duties.